THE FIRST FINDING OF CARBONATITE TUFFS IN CENOZOIC BASALTIC VOLCANO OF SOUTHEASTERN PRIMORYE - Maksimov S.O.; Popov V.K. (My University, 2006)
We found carbonatite tuffs among eruption products of the early Neogene Amba Volcano in southwestern Primorye. The volcanic edifice occupies an area of ~20 km2 in the middle reaches of the Amba River at a distance of 28 km from Amur Bay. The basalts of the stratovolcano base overlie the Permian carbonate and volcanosedimentary rocks and the Triassic arkose sandstones. The basalts are, in turn, overlapped by the upper Miocene volcanosedimentary rocks of the Ust-Suifun Formation and basalts of the Shufan Plateau.
Keywords: Кайнозой::Неоген